2015
DOI: 10.1186/s12955-015-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

One-year trajectories of mental and physical functioning during and after rehabilitation among individuals with disabilities

Abstract: PurposeFirst, to evaluate the trajectories of physical and mental functioning in individuals with chronic disabilities receiving adapted physical activity-based rehabilitation. Second, to determine whether demographic factors, disability group, pain, fatigue and self-efficacy at baseline influenced these trajectories.Research designA prospective intervention study.MethodsThe study included 214 subjects with chronic disabilities who were admitted to a four-week adapted physical activity-based rehabilitation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(46 reference statements)
1
10
1
Order By: Relevance
“…For these reasons, 12 months is considered an important time point for predicting falls and mobility levels in people with stroke. 36,37 To date there has been a paucity of research looking at the factors predicting both falls and mobility levels in people with stroke in the first 12 months after rehabilitation, using the same comprehensive baseline predictor dataset. The aim of this study was to identify factors predicting falls and mobility outcomes in people with stroke in the first 12 months after returning home from rehabilitation.…”
Section: Factors Predicting Falls and Mobility Outcomes In Patients Wmentioning
confidence: 99%
“…For these reasons, 12 months is considered an important time point for predicting falls and mobility levels in people with stroke. 36,37 To date there has been a paucity of research looking at the factors predicting both falls and mobility levels in people with stroke in the first 12 months after rehabilitation, using the same comprehensive baseline predictor dataset. The aim of this study was to identify factors predicting falls and mobility outcomes in people with stroke in the first 12 months after returning home from rehabilitation.…”
Section: Factors Predicting Falls and Mobility Outcomes In Patients Wmentioning
confidence: 99%
“…Nor did we succeed in increasing physical activity from a 1-year perspective. This is in contrast to the results of Preede et al, who found success in improving mental and physical functioning over a longer timeframe after rehabilitation (23). However, increasing physical activity over time is challenging in the context of disability, and van der Ploeg et al (39) also reported a failure to enhance physical activity over time.…”
Section: Discussionmentioning
confidence: 70%
“…The study has a prospective interventional design (ClinicalTrials.gov NCT01788397) and was approved by the Regional Medical Committee for Research Ethics in Norway (S-08837c 2008/21144). The trajectory of physical and mental functioning over one year is reported by Preede et al (23).…”
Section: Study Design and Ethicsmentioning
confidence: 92%
“…(Ware et al, 1996;Ware et al, 2002). The SF12PCS has been used to describe self-reported PF in adults with diverse chronic conditions (Jakobsson, Westergren, Lindskov, & Hagell, 2012;Preede et al, 2015;Resnick & Nahm, 2001;Soley-Bori et al, 2015).…”
Section: Outcome Variablementioning
confidence: 99%